Retracted: Effect of Intelligent Vital Sign Monitoring System on Postoperative Nursing Care of Severe Patients - Imaging, Contrast Media & Molecular (Contrast media and molecular imaging, 2023)
[This retracts the article DOI: 10.1155/2021/1593005.].[This retracts the article DOI: 10.1155/2021/1593005.].